Phygital Transformation and the Modern Customer of Luxury Fashion - Kovář, Jan; Escobar Rios, Andrea; San José Iglesias, Rafael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis explores the integration of phygitisation, a blend of physical and digital experiences, in the luxury fashion industry, examining its impact on modern consumer engagement. Confirmatory factor is used as the method to validate the structural model established in the theoretical part of the thesis. The findings reveal challenges and opportunities in balancing digital integration with maintaining brand exclusivity. The results of this thesis provide practical implications for new luxury communication strategie.
Vedoucí práce: Andrea Escobar Rios
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses